Segodnia v mire . Segodnia v mire . The World Today . Сегодня в мире - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Extension of the Moscow moratorium on nuclear explosions; the trial of Mafia members implicated in a murder; increased repression in South Africa; a drought in the Southern U.S. Featured in the program: Reagan, Ronald Wilson (President of the United States); Abrakhamson, D. (Army General); Botha, Pieter Willem (President of South Africa); Pinochet Ugarte, Augusto (President of Chile) Contributors: Kudrin, Igor' (Anchor) Series description: An information program of the Central Television of the USSR (CT USSR). The hosts were Igor Fesunenko, Valentin Zorin, Farid Seiful-Muliukov, and others. The program was first broadcasted on December 1, 1978 and was broadcasted until 1988. Репортажи: продление Московского моратория на ядерные взрывы; суд над мафиози, замешанными в убийстве; ужесточение репрессий в Южно Африканской Республике; засуха в южных районах США. В программе участвуют: Рейган, Рональд Уилсон (Президент США); Абрахамсон, Д. (Генерал); Бота, Питер Виллем (Президент ЮАР); Пиночет Угарте, Аугусто (Президент Чили) Создатели: Кудрин, Игорь (Ведущий/Ведущая) Описание серии: Информационная телепередача Центрального телевидения СССР. Ведущие — Игорь Фесуненко, Валентин Зорин, Фарид Сейфуль-Мулюков и другие. Первый выпуск передачи вышел в эфир 1 декабря 1978 года. Выходила до 1988 года